2005
DOI: 10.1203/01.pdr.0000147572.57627.ae
|View full text |Cite
|
Sign up to set email alerts
|

Where Does the Developing Brain Obtain Its Docosahexaenoic Acid? Relative Contributions of Dietary α-Linolenic Acid, Docosahexaenoic Acid, and Body Stores in the Developing Rat

Abstract: Docosahexaenoic acid (DHA), a 22-carbon, highly unsaturated, n-3 fatty acid, is important for optimal nervous system function. In this study, designed to quantify how preformed dietary DHA regulates metabolic pathways in vivo, 8-d-old rat pups were divided into four groups and fed artificial rat milk diets. One group was fed formula with deuterium-labeled LNA (d5-LNA) as the only source of n-3 fatty acids, and a second group was fed formula that contained d5-LNA and unlabeled DHA. Two additional groups were da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…The observation of slightly greater levels of 2 H 5 -22:5n-3 and much higher levels of 2 H 5 -22:6n-3 indicates that (1) shorter chain metabolites were very rapidly metabolized to their C22 products, (2) the primary accretion mechanism for 2 H 5 -22:6n-3 was the uptake of preformed molecules from the circulation, or (3) 18:3n-3 and 20:5n-3 are somehow excluded from many phospholipids and are then b-oxidized. The second conclusion is consistent with other studies (26,(41)(42)(43), although it has been proposed that 2 H 5 -22:5n-3 may also be exported from the liver and taken up into the brain (44).…”
Section: Tissue Distribution Of Precursorssupporting
confidence: 92%
“…The observation of slightly greater levels of 2 H 5 -22:5n-3 and much higher levels of 2 H 5 -22:6n-3 indicates that (1) shorter chain metabolites were very rapidly metabolized to their C22 products, (2) the primary accretion mechanism for 2 H 5 -22:6n-3 was the uptake of preformed molecules from the circulation, or (3) 18:3n-3 and 20:5n-3 are somehow excluded from many phospholipids and are then b-oxidized. The second conclusion is consistent with other studies (26,(41)(42)(43), although it has been proposed that 2 H 5 -22:5n-3 may also be exported from the liver and taken up into the brain (44).…”
Section: Tissue Distribution Of Precursorssupporting
confidence: 92%
“…However, both pathways consume carbon from ␣-linolenate so this comparison does provide a reference point from which the impact of dietary or metabolic manipulation on relative synthesis of docosahexaenoate can be evaluated. The brain has a high requirement for docosahexaenoate but not for other n-3 PUFA, so the fact that 13 C incorporation into lipid products of recycling from ␣-linolenate normally exceeds by several fold ␣-linolenate conversion to docosahexaenoate supports other studies showing that incorporation of preformed (consumed) rather than endogenously synthesized docosahexaenoate is likely to be an important way for the brain to obtain docosahexaenoate (18,19). Why carbon recycling occurs so actively in the suckling period and in the face of high demand for docosahexaenoate is still unclear and will require further investigation.…”
Section: Carbon Recycling From ␣-Linolenatesupporting
confidence: 54%
“…When the brain growth spurt (54) occurs in the absence of dietary n-3 fatty acids, the lack of DHA supply results in a marked loss of brain DHA. Recent studies have shown that most of the brain DHA is supplied by preformed DHA when available in the diet (55). In this study, biosynthesis from LNA is an insignificant source of brain DHA because it has been largely eliminated from the diet (Tables 1 and 3) and circulation (56).…”
Section: Discussionmentioning
confidence: 73%